Designing motherhood - Fisher, Michelle Millar; Winick, Amber (The MIT Press, 2021)
"The designed objects that surround us when it comes to menstruation, birth control, conception, pregnancy, childbirth, and early motherhood vary as oddly, messily, and dramatically as the stereotypes suggest. This smart, image-rich, fashion-forward, and design-driven book explores more than eighty designs--iconic, conceptual, archaic, titillating, emotionally charged, or just plain strange--that have defined the relationships between people and babies during the past century. Each object tells a story. In striking images and engaging text, Designing Motherhood unfolds the compelling design histories and real-world uses of the objects that shape our reproductive experiences. Memorable images--including historical ads, found photos, and drawings--illustrate the crucial role design and material culture plays throughout the arc of human reproduction."--Publisher